PENGARUH PEMBERIAN INSENTIF TERHADAP SEMANGAT KERJA KARYAWAN DI PT TIRTA KENCANA TATAWARNA GORONTALO - Putri Rahmadania; Melizubaida Mahmud; Risca Marsanti Halid; Irwan Yantu; Mamang Kasim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Imbalance in compensation systems and high employee turnover in the distribution sector represent critical issues that directly affect company operational effectiveness. This study aims to analyze the effect of incentive provision on employee work morale at PT Tirta Kencana Tatawarna Gorontalo. A quantitative survey method was applied to a saturated sample of 50 employees, divided into 15 respondents for instrument testing and 35 respondents for simple linear regression hypothesis testing. The results prove that incentive provision has a positive and significant effect on employee work morale (t_